RELICS OF THE PAST OR ASSETS FOR THE FUTURE? COMPARING INDIGENOUS TERRITORIES IN CONTEMPORARY BRAZIL AND THE UNITED STATES (Canadian Journal of Native Studies, 2026)
Indigenous Territories (IT) are increasingly viewed as importantassets in the context of climate change and erosion of biodiversity.In Brazil however, they are currently under intense pressureunder the pretext of development. Comparing with the situationof the United States is a good benchmark for what mightcome to Brazil. In this perspective, we first present the historicalprocesses that led to the recognition of IT, then contrast thestructure of IT in both countries from a juridical, administrativeand geographical point of view, and finally point out how issuesrelated to economic development play out in both cases.